Inventory of alien marine species of Cyprus (2009) - S. KATSANEVAKIS; K. TSIAMIS; G. IOANNOU; N. MICHAILIDIS; A. ZENETOS (Mediterranean Marine Science, 2009)
An updated inventory of alien marine species from coastal and offshore waters of Cyprus is presented. Records were compiled based on the existing scientific and grey literature, including HCMR database of Mediterranean alien species, technical reports, scientific congresses, academic dissertations, and websites, as well as on unpublished/personal observations. The listed species were classified in one of five categories: established, invasive, casual, cryptogenic, and questionable. The mode of introduction and the year of first sighting were also reported for each species. Eight new records based on personal observations of the authors were reported (Chondria coerulescens, Neosiphonia sphaerocarpa, Enchelycore anatina, Lagocephalus spadiceus, Lagocephalus suezensis, Scomberomorus commerson, Sillago sihama, and Sphoeroides pachygaster). Nine species, previously reported as aliens in Cypriot waters, were excluded from the inventory for various reasons. Ten established species were characterized as invasive (Caulerpa racemosa var. cylindracea, Cerithium scabridum, Strombus persicus, Trochus erythraeus, Brachidontes pharaonis, Pinctada radiata, Fistularia commersonii, Lagocephalus sceleratus, Siganus luridus, and Siganus rivulatus) as they have a substantial impact on biodiversity and/or local economy. The impact of alien marine species in Cyprus is expected to grow in the close future, and further effort directed towards recording alien invasions and their impact will be needed.